The right to freedom of peaceful assembly in the digital environment of society - Sambor, Mykola (ScienceRise: Juridical Science, 2022)
This research is devoted to the study of the peculiarities of human use of the right to freedom of peaceful assembly in Ukraine and the exercise of this right in the digital environment. The article examines the forms of exercising the right to freedom of peaceful assembly, the peculiarities of their definition in the digital environment in social networks and messengers, the content of this right at the present stage of development of civil society in Ukraine. The freedom to exercise this right in the digital environment is substantiated by the democratic principles of society and the spheres of its existence, in particular digital existence, using the means of telecommunication available to members of Ukrainian society. It is argued, that the right to freedom of peaceful assembly in the digital environment has several basic forms: 1) subjective form of dissemination of information, among subjects who can see the content of the page of a person, which does not provide a specific goal of forming like-minded people and uniting their interests; 2) creation of special groups, networks, which have the immediate goal of attracting and uniting the sole purpose of a certain group of people. The digital environment, which in life is increasingly absorbing people, requires detailed study by legal scholars, because along with the freedom to use these achievements of scientific and technological progress, this area needs quality regulation through a universal regulator - law, relations within it primarily by limiting the state's influence on the freedom of existence and development of the individual and the rights, associated with it, as well as creating decent conditions for the digital development of the individual, his/her freedom and dignity. The exercise of the right to freedom of peaceful assembly in the digital environment depends on the behavior and decisions of public authorities and local governments, as well as on the administrators of relevant social networks. If the first (public authorities) can restrict the work of social networks, the administrators who under certain conditions should be considered as representatives of public administration in the social network can act as censors of the right to freedom of peaceful assembly, using their powers to deleting certain posts, blocking the work of social pages. Unfortunately, the peculiarities of the exercise of these powers in the field of ensuring the right to freedom of peaceful assembly do not find the necessary and sufficient legal regulation, which negatively affects the right to freedom of peaceful assembly in the digital environment, the possibility of its freedom and participation conditions of an unlimited number of participants in such meetings. This is due to the lack of doctrine of understanding the content of the right to freedom of peaceful assembly in the digital environment and forms of its implementation, the composition of relations, in which this right is exercised